Reaching Entrepreneurs through Alternate Models : Lessons from Virtual Incubation Pilots - World Bank Group (Washington, DC, 2014)
Entrepreneurship is an essential component of a growing and dynamic economy. It is a key driver of competition, innovation, and net job creation. The founders of these enterprises can innately gravitate toward cities or hubs that provide them with the resources needed to start or grow their businesses. A 2013 report by Endeavor on what attracts entrepreneurs to cities (What Do the Best Entrepreneurs Want in a City?) noted that entrepreneurs are able to find relevant talent, resources, access to customers and suppliers, and often incentives such as lower taxes and business-friendly regulations in metropolises. infoDev focuses on enabling the start-up and growth of innovative enterprises. infoDev designed a small pilot project to test the merits and values of virtual incubation, recognizing that many innovative entrepreneurs in emerging and developing markets may be situated in less urban areas and that often even the more developed cities lack access to basic resources, such as access to Internet, electricity, or other services and talent. Virtual incubation aims to bring the range of services and tools provided by traditional business incubation to the entrepreneur, in contrast to the entrepreneur availing those services and tools at a fixed location. In addition, understanding that an entrepreneur may have varying needs, virtual incubation provides a more diverse range of these services and tools. This includes outreach services, drop-in services and facilities, online tools, consultancy, mentoring, and networking. The pilot project focused on Vietnam and aimed to assess the cost-effectiveness, sustainability, and impact of services and tools provided to entrepreneurs through this intervention. The pilot comprised a number of activities, including the development of a new generation of entrepreneurs in the country, the establishment of angel networks, the dissemination of best practices, and the expansion of entrepreneurial networks and communities across major hubs in Vietnam.